2008
DOI: 10.2135/cropsci2006.12.0770
|View full text |Cite
|
Sign up to set email alerts
|

Antibiosis Resistance of QTL Introgressive Soybean Lines to Common Cutworm (Spodoptera litura Fabricius)

Abstract: To develop soybean [Glycine max (L.) Merr.] cultivars resistant to common cutworm (CCW; Spodoptera litura Fabricius), it is important to clarify the effects and genetic characteristics of quantitative trait loci (QTLs) for resistance. In a prior study, we detected two QTLs, named CCW‐1 and CCW‐2, for resistance to CCW in a resistant germplasm, ‘Himeshirazu’. Other researchers detected a major QTL for herbivorous insect resistance in PI 229358. Here we constructed near isogenic lines (NILs) of the QTLs via recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
2
25
0
1
Order By: Relevance
“…The effect of another QTL (around Satt567) in LG-M that has been detected in Himeshirazu and named CCW-2 is also evident (Table 3). Komatsu et al 24 confirmed that this Himeshirazu allele actually suppressed the growth of CCW larvae and the effect equaled that of the other resistance gene in LG-M (around Sat_258). In addition, no interaction was detected between the resistance alleles of the QTL.…”
Section: Validation Of Insect Resistance Qtlsmentioning
confidence: 88%
See 3 more Smart Citations
“…The effect of another QTL (around Satt567) in LG-M that has been detected in Himeshirazu and named CCW-2 is also evident (Table 3). Komatsu et al 24 confirmed that this Himeshirazu allele actually suppressed the growth of CCW larvae and the effect equaled that of the other resistance gene in LG-M (around Sat_258). In addition, no interaction was detected between the resistance alleles of the QTL.…”
Section: Validation Of Insect Resistance Qtlsmentioning
confidence: 88%
“…Zhu et al 56 also confirmed the effect of a PI229358 allele, and located the gene between Sat_258 and Satt702, which represents a span of 0.52 cM. Komatsu et al 24 reported 2 . An LOD score of 3.53 was used for the QTL detection threshold based on a Type I error rate of 5%.…”
Section: Validation Of Insect Resistance Qtlsmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, several efforts have been initiated to better characterize and eventually clone the major gene(s) responsible for insect resistance in soybean. Rector et al (1998Rector et al ( , 2000 used restriction fragmentlength polymorphism markers to identify a major quantitative trait locus (QTL) controlling both antixenosis (negative influence on insect preference and/or feeding) and antibiosis (adverse effects on one or more biological systems of insects) on linkage group M. This QTL, named QTL-M, was confirmed in different soybean backgrounds (Komatsu et al 2008;Walker et al 2004;Zhu et al 2006Zhu et al , 2008. Zhu et al (2006) fine-mapped QTL-M to an approximately 0.5-cM interval flanked by Sat_258 and Satt702 through genotyping and phenotyping recombinant substitution lines identified from advanced backcross progenies.…”
Section: Introductionmentioning
confidence: 99%